Interprofessional collaboration between hospital-based palliative care teams and hospital ward staff: A realist review - Louana Moons; Fouke Ombelet; Mieke Deschodt; Maaike L. De Roo; Eva Oldenburger; Inge Bossuyt; Peter Pype (PLoS ONE, 2025)
Introduction To ensure high quality in-hospital palliative care delivery, we need a deeper understanding of the interprofessional collaboration processes between palliative care teams (PCTs) and hospital ward staff. This realist review aims to unravel the relationships between contextual (C) factors, mechanisms (M), and outcomes (O) related to this interprofessional collaboration process. Methods This realist review employed an iterative, theory-driven approach which led to the development of a refined program theory explaining how, for whom, and under which conditions interprofessional collaboration between PCTs and hospital ward staff contributes to quality of care. On April 21 st , 2023, five electronic databases were searched for relevant articles published between January 2013 and April 2023. Data screening and extraction was carried out by two independent researchers. Data-analysis was a two-phase iterative process to develop an overarching CMO-model and ground this model within third-generation cultural-historical activity theory (CHAT). Results We identified 10 recurrent mechanisms contributing to the process of interprofessional collaboration and several moderating factors influencing ward staff’s willingness to initiate PCT involvement. Contextual factors at both ward staff and PCT levels triggered mechanisms related to awareness, feelings, perspectives, and expectations, shaping outcomes for ward staff, PCTs, patients, and relatives. Notable outcomes included improved patient understanding of their disease, relatives’ increased satisfaction with care, greater PCT involvement, and a sense of relief among ward staff. The CHAT-analysis revealed the interplay between expectations, roles, and beliefs in shaping interprofessional collaboration. Dual effects of mediating artifacts, such as palliative care training and time constraints, were observed depending on context, further illustrating the complexity of collaborative practices. Ultimately, this realist review emphasized the need for hospital decision-makers to acknowledge the multidimensional aspects of palliative care and foster a sense of partnership between PCTs and ward staff to optimize IPC. A refined program theory was developed to guide future interventions. Conclusion This realist review highlights the complexity of interprofessional collaboration between PCTs and ward staff, emphasizing the importance of tailored approaches that address specific contextual needs, expectations, and norms. Strengthening positive attitudes, clarifying roles, and fostering partnerships can enhance interprofessional collaboration, ultimately improving palliative care quality in hospital settings.